Meet MicroCode: a Live and Portable Programming Tool for the BBC micro:bit - Hartley, Kobi; Rubegni, Elisa; Underwood, Lorraine; Finney, Joe; Ball, Thomas; Hodges, Steve; Anderson, Eric; Halleux, Jonathan "Peli" de; Devine, James; Moskal, Michal (23rd annual ACM Interaction Design and Children (IDC) Conference, 2024)
Physical computing has emerged as an effective approach to introducing computing and coding to students. One of the most popular enabling tools is the BBC micro:bit, well-known for its positive impact on teaching programming and driving engagement in the classroom. We extend these benefits by developing a new approach to coding with micro:bit: MicroCode. Unlike other experiences, MicroCode couples the micro:bit with a low-cost handheld accessory to enable live and portable programming via an on-device visual programming language; no separate host computer is needed. We present the design of MicroCode and the findings of a study in which we investigated teachers’ perspectives and children’s experiences. We interviewed five primary school teachers and evaluated MicroCode with 60 children aged 10-11. Our findings show that MicroCode raised children’s engagement and stimulated the development of a strong sense of agency, while teachers felt empowered to adopt situated and cross-curricular learning approaches.